Retinal ganglion cell protection against endothelin-1-induced injury by magnesium acetyl taurinate in rats / Dr. Sabrilhakim Sidek … [et al.] - Agarwal, Renu; Nikolayevich lezhitsa, Igor; Mohd Ismail, Nafeeza; Krasilnikova, Anna; Mohd Arfuzir, Natasha Najwa (Research Management Institute (RMI), 2014)
Glaucoma, the leading cause of irreversible blindness, is characterized by apoptotic death of retinal ganglion cells (RGCs). Elevated levels of endothelin1 (ET1), a potent vasoconstrictor, have been detected in the eyes and plasma of glaucoma patients. Increased endothelin 1 causes retinal ischemia increased expression of nitric oxide synthase (NOS) isoforms and oxidative stress, which culminate into RGC apoptosis. Considering the vasodilating, and antioxidant properties of magnesium acetyltaurinate (MgAT) we hypothesized that it can prevent endothelin 1-induced vasospasm, improve retinal perfusion and reduce retinal oxidative stress by altering expression of 3 isoforms of NOS. Rats received single intravitreal injection of vehicle/ET1/ET1 with MgAT. Subsequently, histopathological examination of optic nerve were done to detect the extent of optic nerve damage. Immunochemical detection of NOS isoforms and estimation of NO and antioxidants was done in retina. It was observed that MgAT reduces retinal and optic nerve damage. This neuroprotective effect of MgAT was associated with reduced expression of NOS1 and 2, increased expression of NOS3 and reduced retinal oxidative stress. The results of this study were published in a Q1 journal and were presented in 2 national and 3 international conferences. One student has completed her Master's research work and has been promoted to PhD.